A fundamentação do conceito de possibilidade objetiva na metodologia weberiana - Custódio, Henrique Florentino Faria (2012)
This dissertation investigates the basis for the concept of objective possibility elaborated by Max Weber in his work Critical Studies in the Logic of the Cultural Sciences. The second section entitled Objective Possibility and Adequate Causation in the Causal Consideration of History is especially examined in this paper. In the first part of this work, the aim was to analyze the basis for the concept of objective possibility in Weber‟s methodology, which basically refers to a method of causal imputation applied to the action sciences. Thus, the initial purpose of this study was to demonstrate that in Weber‟s methodology, the evidence produced by the researcher by means of the construction of an ideal type, which, although more than adequate regarding meaning, does not yet possess the conditions to be objectively valid. For the analysis to be scientifically valid, control of the interpretative comprehension of meaning is necessary, because beyond being adequate regarding meaning, the research work also has to be causally adequate. In the second part of this work, the judgment of objective possibility was investigated as an instrument proposed by Max Weber to evaluate the probability that a cause favors or not the emergence of a real fact. This logical-methodological operation is a procedure performed in a series of steps which fall within two limit cases: the adequate cause and the accidental cause. Using these concepts as a starting point, an effort was made to demonstrate that the logical-methodological purpose of the causal sense connection, constructed from the concept of objective possibility, was actually to control the comprehensive interpretation of meaning.